A Comparison of the Academic Performance of College Bound High School Students in Regional vs. Community High Schools in Connecticut - Joseph Patrick Cullen (Arizona State University, 2010)
Consolidated Regional High Schools (RHSs) have replaced traditional Community High Schools (CHSs) in many nonmetropolitan communities. Consolidation purports to offer cost savings that, in theory, enable nonmetropolitan districts to provide a wider array of instructional opportunities to their students. Nonetheless, critics argue that the benefits of consolidation do not outweigh the costs. This inquiry adds to this discussion an examination of differences in performance on the 2006 - 2008 SAT I between RHS and CHS students in Connecticut. Results suggest that RHS students outperformed their CHS counterparts on 15 of 16 points of comparison. Four of these differences reaching statistical significance.